Characterizing genetic variation of adrenergic signalling pathways in Takotsubo (stress) cardiomyopathy exomes. (8th August 2014) - Goodloe, Adele H.; Evans, Jared M.; Middha, Sumit; Prasad, Abhiram; Olson, Timothy M.
<x xml:space="preserve">Abstract</x> Aims Exome sequencing was used to genotype comprehensively a Takotsubo (stress) cardiomyopathy (TC) cohort, enabling investigation of a vast 486 gene network for adrenergic signalling. Methods and results Twenty‐eight TC subjects, including a mother–daughter pair and five recurrent cases, underwent whole‐exome sequencing. Frequencies of 17 common, functional adrenergic polymorphisms were statistically similar to those of population controls. Filtering for rare, predicted‐deleterious, catecholamine/adrenergic signalling variants revealed heterozygosity in 55 genes in TC cases and 59 genes in healthy controls. Overall allele burden was similar and did not discriminate clinical variables among TC subjects, but gene identities were largely cohort specific, and TC cases were enriched for variants within functional domains (68% vs. 48%, P = 0.031). Two‐thirds of TC cases carried more than one filtered adrenergic pathway variant, and 11 genes harboured a variant in ≥2 cases. The mother–daughter pair shared missense variants in highly conserved functional domains of ADH5, CACNG1, EPHA4, and PRKCA. An adrenergic pathway‐independent analysis of the cohort exposed no common gene for TC. Conclusions Overall, these data support genetic heterogeneity in TC susceptibility and a likely polygenic basis, conferring a cumulative effect on adrenergic pathway dysregulation in a subset of individual subjects. Study of larger cohorts and non‐coding regulatory regions is warranted to define genetic risk factors for TC further.